The Impact of Tidal Flooding on Decreasing Land Values in the Areas of Tugu District, Semarang City - Westi Utami; Yuli Ardianto Wibowo; Fajar Buyung Permadi (School of Postgraduate Studies, Diponegoro Univer, 2021)
Semarang City as one of the areas on the north coast has a serious problem related to tidal flooding. The impact of this disaster has implications for changes in land use, a decrease in environmental quality and health, the emergence of slum settlements, a decrease in income and also a decrease in land value. This study aims to map the impact of tidal flooding on changes in land values based on the Land Value Zone Map (ZNT) and map land prices based on spatial data analysis. The study was carried out through spatial analysis by overlaying (join intersection) the 2014, 2016, 2018 and 2019 ZNT maps to determine changes in land value, while mapping land prices, especially in Mangunharjo Village, was based on land use maps, positive accessibility (road network) and negative accessibility (prone flood rob). The results of the study show that land which is permanently affected by tidal flooding and cannot be used anymore makes it a lost / destroyed land, while periodically inundated land has experienced a price decline in the range of Rp 100.000 – 200.000, -/m2. Meanwhile, the results of the study from the ZNT map for 2014 to 2019 show a very significant difference in price between zone 1 and a price increase of ± Rp 3.500.000; zone 2 price increase ± Rp 575.000, -, zone 3 at a price range of Rp 385.000, and zone 4 as the tidal flood prone zone only experienced an increase of Rp 250.000,-. In this context, the variable of tidal flooding vulnerability greatly affects the stagnation of land prices and even decreases in land prices, while the positive accessibility variable is the location of land on national and local roads that has experienced a very high price increase.